Tasks, tools, and mediated actions – promoting collective theoretical work on algebraic expressions - Eriksson, Inger; Fred, Jenny; Nordin, Anna-Karin; Nyman, Martin; Wettergren, Sanna (NOMAD Nordic Studies in Mathematics Education, 2021)
The aim of this article is to exemplify and discuss what teachers using learning activity need to consider when planning and supporting students’ collective theoretical work on algebraic expressions. Data are from two iteratively developed research lessons in two grade 7 classes. The analysis focuses on students’ tool-mediated actions, the mathematical content processed, how the content is dealt with, and on identifying the crucial aspects that enable collective theoretical work. The result provides examples of how the content of the task, its design, and its tools, as well as the teacher’s and students’ tool-mediated actions are crucial factors in the promotion of collective theoretical work.